Proteomics of vitreous in neovascular age-related macular degeneration - Nobl, Matthias Johannes; Reich, Michael; Steliyanova Dacheva, Ivanka; Siwy, Justyna; Mullen, William; Schanstra, Joost P.; Choi, Chul Y.; Kopitz, Jürgen; Kretz, Florian Tobias Alwin; Auffarth, Gerd U.; Koch, Frank; Koss, Michael Janusz (Experimental eye research, 2016)
Neovascular age-related macular degeneration (nAMD) has been described as a predominantly inflammatory and proangiogenic retino-choroidal disease. Vitreous humor (VH) is the adjacent and accessible compartment which, due to the vicinity to the retina, might best represent changes of protein-based mediators of nAMD. The aim of this clinical-experimental study was to analyze the nAMD associated VH proteome of previously untreated patients whilst taking different groups of nAMD into account, based on their clinical presentation (clinical diagnosis groups). Electrophoresis coupled online to mass spectrometry (CE-MS) as well as liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS) were used to analyze VH of 108 nAMD patients and 24 controls with idiopathic floaters. A total of 101 different proteins with at least two unique peptides could be identified. Using a stringent statistical analysis with implementation of the closed test principle, we were able to identify four proteins that may be involved in the pathophysiology of nAMD: Clusterin, opticin, pigment epithelium-derived factor and prostaglandin-H2 d-isomerase. Using independent samples, ROC-Area under the curve was determined proving the validity of the results: Clusterin 0.747, opticin 0.656, pigment epithelium-derived factor 0.514, prostaglandin-H2 d-isomerase 0.712. In addition, validation through ELISA measurements was performed. The identified proteins may serve as potential biomarkers or even targets of therapy for nAMD.